Analisis potensi pengembangan instalasi gizi Rumah Sakit Umum Banyumas menjadi profit center - Wahyanto Wahyanto; Hamam Hadi; Sigit Riyarto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: A hospital is supposed to be self-financed. Nutrition installation as one of units in the hospital is categorized as a cost center unit. It may be changed into a profit center unit if it is developed by providing foods for staff, students and patients’ families.Objectives: To know feasibility of nutrition department development potential of Banyumas Hospital through provision of food service for staff, students and patients’ families in order to contribute for hospital income.Methods: Primary data were collected through questionnaires to know: willingness to pay for from staff, students and patients’ families and commitment of nutrition installation staff; and through focus group discussion to know the commitment of hospital management. Secondary data were obtained from non-experiment observation at nutrition installation and hospital secretariat. Nutrition service development feasibility was viewed from market, commitment of staff and hospital management, and technical aspects.Results: Result of the study showed than potential of nutrition department development to become a profit center by serving foods for staff, students and patients’ families was feasible to implement viewed from: market aspect, there was definite potential market, willingness and capacity to pay, high interest to become customers and marketing mix control; Investment criteria, Net Present value was as much as Rp166,333,504.04, Internal Rate of Return Value was 81.9%, Pay Back Period was 9 months, and Break Even Point was 2 years 10 months and 24 days; Nutrition Installation staff and hospital management commitment was high; Technical aspect, location, raw material resources, manpower, production capacity and facilities were justified.Conclusion: Nutrition department development was feasibly potential to be implemented.